Biogas production from blends of fonio husk and donkey dung via anaerobic digestion for sustainable development - Harrison, Ogala; Ayodeji Rapheal, Ige (International Journal of Advanced Chemistry, 2020)
There is growing public concern over potential impact on environmental quality caused by animal wastes. Anaerobic digestion, a biological conversion process can be used to obtain energy from biologicall wastes. This study explored the production of biogas from co-digestion of fonio hus and donkey dung using anaerobic biological conversion. The digesters were labeled as; digester A –Fonio husk only, digester B - donkey dung only, digester C – Fonio husk (300g) and Donkey Dung (200g), digester D – Fonio husk (200g) and donkey dung (300g). Proximate analysis of the substrates before and after digestion were determined such as total solids (TS), volatile solid, carbon content, nitrogen content, ash content, etc., and pH before and after digestion process. The biogas produced during this period was collected by water displacement method and subsequently measured. The results showed that Fonio husk in bio-digesters A and B gave a cumulative average biogas volume of 4972 ml and 5222 ml (week 3) while pig dung in bio-digesters C and D gave a cumulative average biogas volume of 5564 ml and 5978 respectively (week 3) within three weeks of fermentation. The digester is capable of producing 0.007m at average working temperature of 320C. Digester D produces higher volume of biogas as a result of improved nutrient provide by donkey dung as shown in the results obtained from the proximate analysis and has the best neutral pH, there was a reduction in the startup time.